Optica Advanced Photonics Congress 2022 2022
DOI: 10.1364/sppcom.2022.spth1i.2
|View full text |Cite
|
Sign up to set email alerts
|

FPGA-based Optical Kerr Effect Emulator

Abstract: We propose a digital emulator of the optical Kerr effect, suitable for FPGA implementation. In addition, we study a combined PMD and Kerr emulator implementation with respect to DSP hardware aspects such as fixed-point performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…DSP slices are the main resource bottleneck. However, while the equalizer uses 79.72% of DSP slices, there is still enough room for further adding an on-board PMD-Kerr emulator [16], enabling a complete real-time test platform. Although the time-multiplexed computing units save considerable HW resources in, e.g., the linear BP layers, it is clear that the BP HW consumes more resources than the FP HW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSP slices are the main resource bottleneck. However, while the equalizer uses 79.72% of DSP slices, there is still enough room for further adding an on-board PMD-Kerr emulator [16], enabling a complete real-time test platform. Although the time-multiplexed computing units save considerable HW resources in, e.g., the linear BP layers, it is clear that the BP HW consumes more resources than the FP HW.…”
Section: Resultsmentioning
confidence: 99%
“…4) supplies the equalizer's VHDL model with input data cycle by cycle and the VHDL output is verified with system-level reference data. Forward Propagation (Inference): Running at 2 samples/symbol, the FP HW uses short time-domain filters [14,15] and a HW-friendly Kerr layer [16] to simplify implementation. Since all HW is pipelined for throughput, the FP HW needs to use delays implemented as shift registers (see Fig.…”
Section: Hardware (Hw) Implementationmentioning
confidence: 99%
“…Recently, several field-programmable gate array (FPGA) implementations of ANN-based nonlinear equalizers have been demonstrated [9,10]. One implementation realized both the equalization and training stages within the same FPGA simultaneously [ 11]. In our research group, we demonstrated complex-valued ANN-based nonlinear equalizers, which showed improved learning speed and reduced computational complexity compared to a conventional real-valued ANN [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to most previous works [6]- [8], we do not only propose an optimized implementation of the ANN's forward pass (FP) but also tackle the challenges of implementing the backpropagation algorithm on the FPGA, which enables online retraining on the edge device itself, to adapt for varying channel conditions. A related approach is also presented in [9], but contrary to our work their model is based on the split-step solution of the Manakov-PMD equation instead of an ANN, thus it is not channel-agnostic. Further, it is trained in a supervised way.…”
Section: Introductionmentioning
confidence: 99%